Development of Programmable Logic Controller (PLC) Trainer Learning Media for Industrial Automation - Widinata, Fandi; Wirawan, I Made (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This research aims to develop learning media through PLC trainers and job sheets to support practical learning in the subject of Programmed Control Systems at Vocational High School (SMK) Negeri 1 Singosari. The background of this research is the limited real practice media, where students previously only relied on simulations, causing a gap between understanding theory and practical skills. The development model used in this research follows the ADDIE framework, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data was collected through interviews, observations, expert validation, and user trials involving 11th-grade students of Industrial Automation Engineering of SMK Negeri 1 Singosari. The results showed that the trainer and jobsheet developed were declared "very feasible" based on the validation of media experts (95.8%), material experts (93.8%), and student trials in small groups (95.6%) and large groups (96.6%). Revisions were made based on expert input, such as adding diodes for safety and evaluation questions on the jobsheet, which improved trial results. The implication of this research shows that integrated and contextual learning media can bridge the gap between theory and practice, improve students' technical competence, and support the achievement of learning objectives.